LOOKER STUDIO DASHBOARD FOR VISUALIZING AND ANALYZING POST-COVID-19 ECONOMIC GROWTH IN LAMPUNG PROVINCE REGENCIES AND MUNICIPALITIES - Aprilia Puspita Sari; Rizki Abdi Utama Abdi Utama; M Said Hasibuan Hasibuan (Journal of Computer Science and Information Technology, 2026)
This study aims to develop a Looker Studio dashboard for visualizing and analyzing post-COVID-19 economic growth across regencies and municipalities in Lampung Province and to identify regional economic recovery patterns during the 2019–2024 period. The research method employed was a descriptive quantitative approach using secondary data obtained from the Central Statistics Agency (BPS) of Lampung Province and all regencies/municipalities through dynamic tables and official publications. The collected data were processed through cleaning, validation, integration, and visualization stages using Google Looker Studio. The results show that the developed dashboard successfully provides interactive visualizations of economic growth rates and Gross Regional Domestic Product (GRDP) contribution shares across regions. The analysis reveals that all regencies and municipalities experienced economic contraction in 2020 due to the COVID-19 pandemic, followed by gradual recovery during 2021–2024. Bandar Lampung Municipality consistently recorded the highest economic growth rates during the recovery period, indicating strong urban economic resilience, while Central Lampung Regency demonstrated the greatest economic stability due to the dominant role of the agricultural sector. In contrast, East Lampung Regency experienced the deepest contraction because of its dependence on the oil and gas sector. The findings also indicate that post-pandemic economic recovery occurred unevenly across regions, reflecting differences in economic structure and adaptive capacity. In conclusion, the Looker Studio dashboard is an effective tool for visualizing and analyzing regional economic growth, providing a comprehensive understanding of post-COVID-19 economic recovery patterns and supporting evidence-based regional development planning and policymaking in Lampung Province.